2010
DOI: 10.1007/s10096-010-0928-9
|View full text |Cite
|
Sign up to set email alerts
|

Significant decline in pneumonia admission rate after the introduction of routine 2+1 dose schedule heptavalent pneumococcal conjugate vaccine (PCV7) in children under 5 years of age in Kielce, Poland

Abstract: International audienceThis study was performed to estimate the effect of heptavalent pneumococcal conjugate vaccine (PCV7) on the pneumonia admission rate in children younger than 5 years of age, after the introduction of routine 2+1 dose schedule immunization. We compared the pneumonia admission rate (number of cases per 1,000 population) 2 years before and 2 years after the introduction of PCV7 in 2006. Only children with radiologically confirmed pneumonia were analyzed. The vaccination rate in the analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 25 publications
3
24
0
2
Order By: Relevance
“…Patrzałek et al investigated the influence of pneumococcal vaccination on the radiologically confirmed pneumonia admission rates in the hospital [8]. The results compare well with the 3+1 PCV7 dosing schedule [35][36][37].…”
Section: Effectiveness Of the Reduced-dose Schedule (2+1) In Childrensupporting
confidence: 54%
See 2 more Smart Citations
“…Patrzałek et al investigated the influence of pneumococcal vaccination on the radiologically confirmed pneumonia admission rates in the hospital [8]. The results compare well with the 3+1 PCV7 dosing schedule [35][36][37].…”
Section: Effectiveness Of the Reduced-dose Schedule (2+1) In Childrensupporting
confidence: 54%
“…Since PCV7 has been documented to be effective when given in a 2+1 dosing schedule, a few studies have compared the immunogenicity data when PCV13 and PCV7 are given in accordance with this dosing regimen [8,9,12,19].…”
Section: -Valent Pneumococcal Conjugate Vaccine (Pcv13)mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PCV13 is recommended for everyone from the second month of life onward, and PPV23 for persons more than two years old, according to the Summary of Product Characteristics [6]. There are also some local initiatives, as in Kielce city, where the authorities decided to offer free vaccination for all children under two years of age, living within the city borders [7]. Moreover, according to the data provided by the National Institute of Public Health-National Institute of Hygiene, every year the number of parents who decide to vaccinate their children has increased, namely, 139,039 in 2010, 159,166 in 2011 and 173,248 in 2012, children below 15 years old completed their vaccination programs (primary or reinforcing) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[44] In Poland, the two infant doses schedule of PCV7 was found to be efficacious for reduction of CAP in children. [45] A significant impact of pediatric vaccination on reduction in hospitalization for alveolar pneumonia in adults in the US has been recently shown and more than 90% of the reduction in hospitalization for pneumonia attributable to the vaccine is the reduction in disease in adults due to herd protection. [46] The effect of PCV7 on AOM In a randomized clinical trial conducted in Finland in which the bacterial etiology of AOM was determined by myringotomy, the efficacy of PCV7 in preventing culture-confirmed, vaccine serotype AOM episodes was 57% (95% CI, 44-67%): the overall net reduction in AOM caused by any pneumococcal serotype was 34% (95% CI, 21-45%).…”
Section: The Effect Of Pcv7 On Invasive Diseasementioning
confidence: 99%